Peran Guru dalam Pendidikan Karakter : Meneladani Ajaran Nabi Muhammad SAW dalam pendidikan karakter pada murid. - Fawzy, Hamida Rizka (Maliki Interdisciplinary Journal, 2024)
This article discusses the role of educators in shaping a child’s character, emphasizing the importance of selecting the right teachers and educational institutions. In the era of globalization and modernization today, the phenomenon of violence, brawls, and moral decadence among teenagers has become a very concerning issue. The main cause of this problem is the lack of directed character education. Character education in schools heavily relies on the role of teachers as role models and guides who impart noble values, as exemplified by the Prophet Muhammad SAWin Islamic teachings. A teacher with noble character will become a positive role model for students, thereby expected to reduce negative behavior and improve the moral quality of the younger generation. This research uses library methods to collect and analyze data from various sources related to the role of teachers in character education. The results of this research are expected to provide insights for parents, educators, and the community to better understand the importance of character education in shaping a generation with noble morals.